2017
DOI: 10.1007/s12253-017-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

Familial Acute Myeloid Leukemia and Myelodysplasia in Hungary

Abstract: Although genetic predisposition to haematological malignancies has long been known, genetic testing is not yet the part of the routine diagnostics. In the last ten years, next generation sequencing based studies identified novel germline mutations in the background of familial aggregation of certain haematologic disorders including myelodysplastic syndromes (MDS) and acute myeloid leukaemia (AML). This is supported by the fact that the myeloid neoplasms with genetic predisposition represent a new category in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…We excluded 77 publications, including 41 animal studies, 20 about irrelevant subjects, 13 reviews, and three in languages other than English and Chinese. The remaining 30 were next given full-text reviews and all were considered eligible for this study, including nine case series, 12 , 14 21 11 case reports, 22 – 32 four reports about DDX41 -related solid cancers, 33 – 36 and six rare case reports 37 42 ( Figure 1 ). No extra study was identified from the references listed in the relevant reviews and the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 77 publications, including 41 animal studies, 20 about irrelevant subjects, 13 reviews, and three in languages other than English and Chinese. The remaining 30 were next given full-text reviews and all were considered eligible for this study, including nine case series, 12 , 14 21 11 case reports, 22 – 32 four reports about DDX41 -related solid cancers, 33 – 36 and six rare case reports 37 42 ( Figure 1 ). No extra study was identified from the references listed in the relevant reviews and the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…DDX41 mutation was negatively detected in Hungary. 40 One hundred and thirty-five patients had both germline and somatic DDX41 mutations.…”
Section: Resultsmentioning
confidence: 99%
“…A familiáris MDS/AML kialakulásának hátterében számos autoszomális domináns módon öröklődő mutációk állnak, melyek alapján négy szindrómát különítünk meg: 1) a CEBPA-pozitív familiáris MDS/AML-t, 2) a GATA2-pozitív familiáris MDS/AML-t, 3) a familiáris vérlemezke-funkciózavar kapcsán kialakuló MDS/AML-t RUNX1-pozitivitással, és 4) a csontvelő-kimerüléssel járó kórképek TERT és TERC génmutációval, illetve egyéb gének, mint a ANKRD26, ETV6, DDX41, SRP72 stb.) eltéréseivel [29,30]. A fentiek tükrében bizonyos életkor alatt (pl.…”
Section: Cebpa-mutációkkalunclassified
“…A fentiek tükrében bizonyos életkor alatt (pl. 40 év) érdemes lenne a CEBPA-mutáció csíravonalbeli eredetét tesztelni, mivel ezen öröklődő mutációkat hordozó esetek nagy részét hazánkban még nem ismerjük, a genetikai eltérések időbeni felismerése pedig biztosíthatja a vizsgált személy megfelelő nyomon követését, a csontvelő-transzplantáció egyéni elbírálását és a tünetmentes vérrokonok kiszűrését [29,30]. Amennyiben a CEBPA-mutáció örökletesnek bizonyul, a beteg testvére nem lehet donor.…”
Section: Cebpa-mutációkkalunclassified
“…Trombositopeninin en önemli nedenleri; kemik iliğinde yetersiz üretim ve trombosit ömrünün kısalmasıdır. (5) Düşük sayıda granül içeren, dev boyutta, fonksiyon bozukluğu gösteren trombositlere rastlanabilir. (6) Periferik kanda, ciddi lökopenisi olan hastalar dışında miyeloblastların görülmesi beklenir.…”
Section: Introductionunclassified